The Application of Problem-Based Learning and Think-Pair-Share Models to Enhance Students’ Creative Thinking Skills at SMP Negeri 6 Watampone - Darwis, Kurniati; Halidin, Ali; Arisal A, H. (Sekolah Tinggi Agama Islam Al-Furqan, Makassar - Indonesia, 2025)
This study aims to analyze the influence of the Problem-Based Learning (PBL) and Think-Pair-Share (TPS) models on students’ creative thinking skills in Islamic Education at SMP Negeri 6 Watampone. Creative thinking is an essential competency in the Merdeka Curriculum that must be developed through innovative learning models integrating Islamic values with contemporary methodologies. The study employed a quantitative approach with an ex post facto design, involving 60 randomly selected seventh-grade students. Data were collected using questionnaires on the implementation of PBL and TPS, as well as creative thinking tests measuring four indicators: fluency, flexibility, originality, and elaboration. Data were analyzed using descriptive statistics and multiple linear regression with the assistance of Jamovi software. The results showed that the implementation level of PBL reached a Respondent Achievement Level (RAL) of 77.46%, while TPS achieved 73.7%, both categorized as high, with PBL demonstrating more consistent implementation. Students’ creative thinking was dominated by fluency (69.95%) and originality (69.4%), while elaboration was the main challenge (50.5%). PBL had a significant effect on creative thinking (R² = 29.3%, p < 0.001), TPS contributed (R² = 26%, p < 0.001), and their combined effect reached R² = 33% (p < 0.001), indicating a superior synergistic influence. This study confirms that the integration of PBL and TPS is effective in fostering students’ creative thinking in Islamic Education at SMP Negeri 6 Watampone. It further recommends optimizing elaboration skills through targeted programs and systematic, sustainable implementation.